"Ті хто натискали на гачок": коменданти НКВС УРСР та УНКВС Київської області у часи "Великого терору" - Бажан, О.; Золотарьов, В. (Краєзнавство, 2016)
У статті вивчаються персоналії виконавців смертних вироків у системі радянських органів держбезпеки УРСР у другій половині 1930- х років. From the very beginning of the Soviet state security bodies the executions of political opponents, “enemies of the people” were assigned to the commandant staff. It was a special caste of the security bodies – VUChKGPU- NKVD. Even until now there has not been found a special legal instrument to regulate these functions. According to the “Regulations of the organizational structure of VChK and its departments and their relationship”, which was approved by the general meeting of VChKemployees on July 11, 1918, it was determined that the Commandant department provides protection of buildings, is responsible for the information desk and the prison. In practice, a person who served as commandant of the NKVD, among other things had to acquire executioner’s skills – he should be able to skillfully manage the firing squad during the procedure of executions. The technology of death penalty in the Soviet Union in the years 1920-1930-ies (the place of execution, burial place of executions, the staff of performers) were rarely the subject of separate scientific researches. There is a lack of biographical researches, which meticulously represent the life and activities of commandants of the NKVD of the Ukrainian SSR. (OleksnndrShashkov, Lev Leliotkin, Oleksndr Liutov, Kuzma Koz’mynykh, Ilia Shchukin) and their deputies (Ivan Nagornyi,Mykhailo Skobliev,Ivan Bolokhin, Naum Turbovskyi, Ivan Gryshyn) that were involved in the executions according to the decisions of extrajudicial bodies in times of “Great Terror”. Basing on the body of archival sources, a number of reference and information resources, the authors tend to reproduce the biographies of the executors. And on the basis of the evidences, ther try to trace how social, historical and situational factors affected the will and actions of certain NKVD officers. В статье исследуются персоналии исполнителей смертных приговоров в системе советских органов госбезопасности УССР во второй половине 1930- х годов.